2013
DOI: 10.1007/s40264-013-0027-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Two Drug Interaction Screening Programmes Analysing a Cross-Sectional Prescription Dataset of 84,625 Psychiatric Inpatients

Abstract: BACKGROUND: Clinical decision support software (CDSS) solutions can automatically identify drug interactions and thereby aim to improve drug safety. However, data on the comparative performance of different CDSS to detect and appropriately classify interactions in real-life prescription datasets is limited. OBJECTIVE: The aim of this study was to compare the results from two different CDSS analysing the pharmacotherapy of a large population of psychiatric inpatients for drug interactions. METHODS: We performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…found sensitivities of 0·71 and 0·72 using pDDIs classified as OpeRational ClassificAtion of drug interactions (ORCA) levels 1–3 as part of the Zürich Interaction System as a silver standard. When changing the silver standard to ORCA 1–2 as part of Zürich Interaction System, sensitivity was 0·52 for ID PHARMA CHECK ® and 0·94 for mediQ . Data indicate the dependance of sensitivity on the definition of clinical relevance as discussed.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…found sensitivities of 0·71 and 0·72 using pDDIs classified as OpeRational ClassificAtion of drug interactions (ORCA) levels 1–3 as part of the Zürich Interaction System as a silver standard. When changing the silver standard to ORCA 1–2 as part of Zürich Interaction System, sensitivity was 0·52 for ID PHARMA CHECK ® and 0·94 for mediQ . Data indicate the dependance of sensitivity on the definition of clinical relevance as discussed.…”
Section: Discussionmentioning
confidence: 96%
“…Clinical decision support systems (CDSSs) can be successfully used to reduce serious potential DDIs (pDDIs) . However, a series of studies have shown that CDSSs differ widely in their ability to identify pDDIs . Vitry et al .…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Multiple resources were used to select the 125 drug interaction pairs. These include studies of potential DDI detected in various healthcare settings [11,[39][40][41][42][43][44], reviews of potential DDI involving psychiatric drugs [23,27,28,[45][46][47], lists of serious drug interactions used in prior testing of drug interaction database programs [48][49][50], and lists of frequently prescribed drugs [51,52]. All 125 drug interaction pairs had at least 1 category rating of major from at least one of the 6 drug interaction database programs.…”
Section: Drug Interaction Pairsmentioning
confidence: 99%
“…Medications used to treat medical conditions can interact with psychotropic medications (Ferrando et al 2010;Sinclair et al 2010;Zorina et al 2013). Many individuals receiving psychiatric treatment are taking multiple medications, and this magnifies the likelihood of drug-drug interactions (Haueis et al 2011;Mojtabai and Olfson 2010;Sandson et al 2005;Thomas et al 2010).…”
Section: Rationalementioning
confidence: 99%